Slums: a sociological retrospect of the city of Dublin - Millin, S. Shannon (Statistical and Social Inquiry Society of Ireland, 1914)
If I required an excuse for my paper, I would quote the words of the Chief Secretary Right Hon. A. Birrell, M.P., in reply to a deputation which recently waited on him in reference to the Dublin Housing Problem:?"As long as people rested content to live surrounded by such things as had been described, they were in a bad way themselves, perhaps even in a worse way than their poorer neighbours, who endured these terrible conditions. The more that was said, and thought, and written on the subject, particularly when there seemed to be a little light lifting over that black veil, the better it would be for all. It was the awakening of public opinion that was, after all, the only security for the remedy of the terrible evils which existed in Dublin." (29th October; 1913).
Read Friday, 23rd January, 1914
Keywords: Poverty; Slums, Dublin; Dublin tenements; Public housing; 314.15